Counseling and Psychotherapy for Marriage Problems: A Scoping Review - Radhiya Bustan; Bagus Riyono; Diana Setiyawati (Green Publisher, 2025)
Assisting married couples in resolving relational issues is essential for maintaining family stability, with psychological interventions such as marriage counseling and psychotherapy playing a key role. Given the wide range of approaches currently in use, further mapping and evaluation are needed to guide the development of more effective interventions. This study conducts a scoping review to systematically identify types of marital problems, contributing factors, and intervention models applied over the past decade. Using the PRISMA-ScR protocol, 2,602 articles were initially retrieved from Web of Science, Scopus, and ScienceDirect databases, with 76 studies meeting the inclusion criteria. The review reveals that common marital issues include poor communication, domestic violence, sexual and intimacy challenges, mental health disorders, cultural clashes, gender role conflicts, infidelity, and socio-economic disparities. These issues often intersect with influencing factors such as religious beliefs, communication styles, emotional regulation, trauma, stress, substance abuse, education, culture, stigma, and social support. The most frequently used intervention model is couple or marriage therapy, with Cognitive Behavioral Therapy (CBT) receiving significant attention for its effectiveness. Other identified approaches include psychodynamic, humanistic-existential, Emotionally Focused Therapy (EFT), mindfulness-based interventions, integrative methods, group-based therapy, and religion-based counseling. However, the literature remains dominated by conventional psychological frameworks, with limited incorporation of religious or spiritual approaches, despite their relevance to many clients. This mapping provides a foundation for researchers and practitioners to design more culturally and spiritually responsive interventions tailored to diverse client needs.